Potensi Sengketa Terkait Keadaan Kahar (Force Majeure) Dalam Kontrak Pengadaan Pemerintah - Sujoko, Ajik (Jurnal Pengadaan Indonesia, 2023)
The potential for disagreement between the parties to accept the event is considered a force majeure event to the contract is very likely to occur. Force major has the potential to occur at every stage of the contract starting from the pre-contract stage, the contract implementation stage, post-contract stage. To minimize the potential for disagreements that will lead to disputes, it is best to understand the potential problems at each stage of the contract related to force majeure. Contract designs or drafts that mention force major clauses in detail and precision are required in contracts in government procurement.